Causes of ventilatory inefficiency in lung resection candidates - Stepan Bartos; Michal Svoboda; Kristian Brat; Marek Lukes; Adam Predac; Pavel Homolka; Lyle J. Olson; Ivan Cundrle (ERJ Open Research)
Introduction Ventilatory efficiency (V′E/V′CO2) has been shown to predict postoperative pulmonary complications (PPCs) in lung resection candidates. V′E/V′CO2 is determined by arterial partial pressure of carbon dioxide (PaCO2) and by dead space to tidal volume ratio (VD/VT). We hypothesised PaCO2 and VD/VT contribute equally to the increase in V′E/V′CO2 in lung resection patients. Methods Consecutive lung resection candidates from two prior prospective studies were included in this post hoc analysis. All subjects underwent preoperative spirometry, cardiopulmonary exercise testing and arterial blood gas analysis at rest and peak exercise. PPCs were prospectively assessed during the first 30 postoperative days, or hospital stay. A t-test, Mann–Whitney U-test and two-tailed Fisher's exact test were used to compare patients with and without PPCs. p-values <0.05 were considered statistically significant. Results Of 398 patients, PPC developed in 64 (16%). Patients with PPCs more frequently underwent lobectomy by open thoracotomy, had longer hospital and ICU length of stay and higher 30- and 90-day mortality. Moreover, patients with PPCs exhibited a higher V′E/V′CO2 ratio both at rest and peak exercise. Both ratios were independently associated with PPCs. At rest, the contribution of PaCO2 and VD/VT to the increase in V′E/V′CO2 ratio in patients with PPCs was 45% and 55%, respectively. At peak exercise, the contribution of PaCO2 and VD/VT to the increase in V′E/V′CO2 ratio was 16% and 84%, respectively. Conclusions VD/VT (V′/Q′ mismatch and/or rapid shallow breathing pattern) is the dominant contributor to the increase in V′E/V′CO2 in lung resection candidates who develop PPCs.